Charge Accumulation and Hysteresis in Perovskite‐Based Solar Cells: An Electro‐Optical Analysis. Issue 19 (27th July 2015) - Wu, Bo; Fu, Kunwu; Yantara, Natalia; Xing, Guichuan; Sun, Shuangyong; Sum, Tze Chien; Mathews, Nripan
<x xml:space="preserve">Abstract</x> Organic–inorganic hybrid perovskite solar cells based on CH3NH3PbI3 have achieved great success with efficiencies exceeding 20%. However, there are increasing concerns over some reported efficiencies as the cells are susceptible to current–voltage (I–V) hysteresis effects. It is therefore essential that the origins and mechanisms of the I–V hysteresis can clearly be understood to minimize or eradicate these hysteresis effects completely for reliable quantification. Here, a detailed electro‐optical study is presented that indicates the hysteresis originates from lingering processes persisting from sub‐second to tens of seconds. Photocurrent transients, photoluminescence, electroluminescence, quasi‐steady state photoinduced absorption processes, and X‐ray diffraction in the perovskite solar cell configuration have been monitored. The slow processes originate from the structural response of the CH3NH3PbI3 upon E‐field application and/or charge accumulation, possibly involving methylammonium ions rotation/displacement and lattice distortion. The charge accumulation can arise from inefficient charge transfer at the perovskite interfaces, where it plays a pivotal role in the hysteresis. These findings underpin the significance of efficient charge transfer in reducing the hysteresis effects. Further improvements of CH3NH3PbI3‐based perovskite solar cells are possible through careful surface engineering of existing TiO2 or through a judicious choice of alternative interfacial layers.